User generated content and the Muslim consumer in cyberspace - Saidin, Aznan Zuhid; Abu Bakar, Elistina (Persatuan Ekonomi Pengguna dan Keluarga Malaysia (MACFEA), 2012)
With the present technological development of the World Wide Web, or ‘Web 2.0’, cyberspace has become a domain for the common user/consumer to join the computer savvy in contributing to the online content on the Internet. This is evident in the popularity of blogs, media sharing and social networking sites that allows the online consumer to also play the role as the content creator. This situation raises some issues concerning privacy, data protection and defamation with the responsibility now being more in the hands of the consumer in exercising self-restraint. For the Muslim consumer, assuming this role and its responsibilities would require some ethical guidance from the Islamic perspective in order to promote a healthy use of cyberspace for the purpose of having better spiritual and social sustainability and quality of life. Issues discussed in this paper warrant further studies that will later lead to the formulation of codes of practices for the online consumer as the content creator.